Experimental and Computational Studies of a Prototype Combustion Chamber for a Power Steam Boiler with a Vertical Precessing Vortex - Boiko E.A.; Semenov I.I.; Lebedev K.V.; Kulichkin A.P. (Problems of the Regional Energetics)
Increasing the efficiency of using fossil fuels at thermal power plants is an urgent task. This problem arises most acutely during the operation of pulverized coal power boilers using flare fuel combustion technologies. The purpose of this work is an experimental and computational study and justification of the technology of low-temperature combustion of coal in a combustion chamber with a vertical precessing vortex and the creation of a prototype combustion chamber for a power steam boiler. To achieve this goal, a study of the process of two-stage coal combustion was carried out, when the first stage of coal combustion is carried out in a pre-furnace with a fluidized bed, and the after-combustion of the products of incomplete combustion of coal is carried out with gas illumination in an after-combustion chamber with a vertical precessing vortex. The relationship between the main design parameters of the combustion chamber and the main operating characteristics of the diffusion vortex has been determined. The most important results are: development and experimental validation of the parameters of the combustion chamber with a vertical precessing vortex; determination of optimal operating modes of the furnace when burning coal and combined combustion of coal and gas; creation of a prototype furnace for a power steam boiler with natural circulation, operating on Kansk-Achinsk coal. The significance of the results obtained lies in the possibility of their use in the design of new or modernization of existing power boilers in order to increase the efficiency, reliability and environmental safety of operation.